INVESTIGATION OF HEPATOCELLULAR CARCINOMA AND FOCAL NODULAR HYPERPLASIA ON TRIPHASIC COMPUTED TOMOGRAPHY (The Research of Medical Science Review, 2025)
Objective: To observe the focal nodular hyperplasia images will be evaluated and contrasted with the hepatocellular carcinoma images in each phase of the triphasic CT scan, the other objective was to evaluate the diagnostic precision of triphasic CT for differentiating FNH from HCC through vascular and anatomical features that distinguish FNH from HCC and finding clinical usefulness for accurate and timely diagnoses with triphasic CT scan results. Study design: It was a cross-sectional study design. Place and duration of study: The study was conducted at THQ Hospital Sadiqabad, Pakistan from August to December 2024. Material and Methods: By adopting cross-sectional study design Thirty-five individuals with FNH and thirty- five with HCC were among the seventy patients studied. In order to find diagnostic signals specific to each illness, the study assessed delayed phase imaging, arterial imaging, and portal venous imaging. Results: About The results revealed that The majority of instances occurred in patients aged 61–80 years (48.57%), followed by 41–60 years (40%), with 57.14% of patients being male and 42.85% being female in the FNH study. Among the complaints were numerous symptoms (40%) and stomach discomfort (25.71%), and 42.85% had a history of declining liver function. During the arterial phase, imaging revealed hyperdense lesions with regular borders in 28.57% of cases and irregular borders in 65.71%. No washout or central scars were found in the delayed phase, and 80% of patients had hypodense lesions during the venous phase.The frequency of HCC peaked in the age range of 41–60 years (45.71%), with 51.42% of men and 48.57% of women affected. Jaundice (5.71%) and stomach discomfort (54.28%) were among the symptoms, while 28.57% had no previous medical history. In the arterial phase, imaging showed hyperdense lesions with irregular boundaries in 82.85% of cases, whereas in the venous phase, it showed isodense lesions in 97.14% of cases. Unfortunately, there was a washout period and also lack of core scarring across all cases. Peak incidence of HCC is noted in males and females aged 41-60 years: of 45.71 percent, 51.42 percent were men and 48.57 were women. The only symptoms which make up the majority of metastasizing cases are jaundice (5.71%) and abdominal pain (54.28%), while 28.57% of those affected have no past medical history. Imaging of the arterial phase revealed hyperdense lesions with irregular boundaries in 82.85% of the cases, whereas for the venous phase isodense lesions were detected in 97.14%. In each case, a washout phase and absence of core scarring were recorded. Conclusion: We concluded that Triphasic CT is important in differentiating between focal nodular hyperplasia (FNH) and hepatocellular carcinoma (HCC). An analysis of the specific image features delivered by artery and portal venous delay phases had led us to locate special diagnostic determinants bearing on each disease. The assessment of diagnostic accuracy with significant specificity and sensitivity between the two liver lesions proved reliable for triphasic CT and was informative for the clinical practice.